Efficient spectrum utilisation in third generation cellular communications systems - Demestichas, P.P.; Demesticha, V.P.; Tzifa, E.C.; Anagnostou, M.E.; Theologou, M.E. (Computers and Communications: Proceedings of the IEEE Symposium on Computers and Communication, Alexandria, Egypt, 1997, 1997)
One of the most central issues in third generation telecommunication systems is efficient spectrum utilisation. This objective has motivated extensive research in the area of channel allocation techniques. The basic version of the channel allocation problem is the following: given a set of channels, the cell structure and the load to be accommodated in each cell, find the optimum allocation of channels to cells, subject to the restrictions concerning the distance of cells, where the same channel can be used. This problem handles a traffic load that is fixed with time. We extend this formulation so as to include time variant traffic loads and, hence, to obtain efficient spectrum utilisation. We consider two approaches to this extension, which are differentiated by the fact that the first involves a total reconfiguration of the channel allocation, while the second only a partial reconfiguration. Both approaches are theoretically formulated and solved. Finally, we present results and draw subsequent conclusions.